Intellectual property in designs - Sykes, John (LexisNexis Butterworths LondonGB, 2005)
Provides an analysis and commentory on the five intellectual property rights potentially subsisting in an innovative design viz. copyright, UK unregistered design rights, UK registered design rights under both the old law and the new law, Community unregistered design rights and Community registered design rights. Summarizes the law in several countries other than the UK.